PENGARUH LEADERSHIP, ORGANIZATIONAL CULTURE DAN COMPETENCY TERHADAP KINERJA KARYAWAN - Kusumaningtyas, Dhevi Dadi; Zusrony, Edwin; Manalu , Gibson; Anzie , Luthfy Purnanta; Asti , Pindo; Permana , Ivan (Dinamika: Jurnal Manajemen Sosial Ekonomi, 2023)
This research aims to see how much influence the leadership, organizational culture and competency variables have on employee performance variables. Data collection uses a questionnaire to obtain answers to research variables and respondent data. The sampling method uses a convenience sampling technique. The respondents were 96 lecturers at the University of Computer Science and Technology in the city of Semarang. The indicators for assessing questionnaire answers use a Likert scale. The data analysis method uses multiple linear regression and is processed using the SPSS 24 application. The research results reveal that the leadership, organizational culture and competency variables have a significant influence on employee performance. The most dominant leadership variable in achieving optimal employee performance for respondents, namely lecturers at the University of Computer Science and Technology.